A fire-resistant shipboard cable

By designing fire-resistant marine cables and adopting specific material composition and structural design, the problem of difficulty in maintaining electrical functions of ship cables during fires is solved, and high fire-resistant performance and normal energization effect in high-temperature environments are achieved.

CN118016361BActive Publication Date: 2025-01-24ZHU ZHOU SHEN TONG DIAN XIN SHI YE YOU XIAN ZE REN GONG SI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410350291.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2025-01-24
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

Ship cables are difficult to maintain electrical functions during fires, which affects escape and self-rescue.

Method used

Design a kind of fire -resistant ship cable, using an external refractory layer, internal refractory layer and refractory filler. The composition of the material includes polyvinyl chloride resin, ABS resin, polyte -containing liquid embedded parts, charcoal black, nanometer aluminum water talc, nano -nano Boron -oxide and nano -oxide, through the combination and structural design of these materials, improve the refractory resistance of cables in high temperature environments.

Benefits of technology

After burning in a 950-1000°C flame for 90 minutes, the cable can still maintain normal energization, reaching Class A standard fire resistance, improving the escape and self-rescue capabilities of people on board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118016361B_ABST
    Figure CN118016361B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electric wires and cables, in particular to a fire-resistant shipboard cable, comprising a cable core, an outer fire-resistant layer, a shielding layer and an outer sheath layer, wherein the cable core consists of a conductor, an inner fire-resistant layer and an inner sheath layer; the outer fire-resistant layer and the inner fire-resistant layer are made of the same material, and the outer fire-resistant layer and the inner fire-resistant layer are made of the same material, and the outer fire-resistant layer and the inner fire-resistant layer are made of the following components in parts by weight: 100-120 parts of polyvinyl chloride resin, 25-35 parts of ABS resin, 5-15 parts of polyionic liquid-containing block copolymer, 40-60 parts of carbon black, 20-30 parts of nano magnesium aluminum hydrotalcite, 5-10 parts of nano boron oxide, 5-10 parts of nano zinc oxide, 1-2 parts of a plasticizer and 1-2 parts of a silane coupling agent. The fire-resistant shipboard cable prepared by the invention can still maintain normal power supply after burning in a flame of 950-1000°C for 90 minutes, exhibits extremely high fire resistance and reaches Class A standards.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electric wires and cables, in particular to a fire-resistant shipboard cable. Background Art

[0002] Ships play a very important role in modern transportation, and cables are like blood vessels and nerves, spread throughout the ship, responsible for power supply, signal control and communication. When a fire occurs, the cables need to be able to maintain electrical functions in a high-temperature combustion environment to ensure the normal operation of the power supply and control system so that people on board can escape and save themselves within an effective time and improve their survivability. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a fire-resistant shipboard cable.

[0004] The technical solutions adopted are as follows:

[0005] A fire-resistant shipboard cable comprises a cable core, an outer fire-resistant layer, a shielding layer and an outer sheath layer, wherein the cable core is composed of a conductor, an inner fire-resistant layer and an inner sheath layer;

[0006] The outer refractory layer and the inner refractory layer are made of the same material, and include the following components by weight:

[0007] 100-120 parts of polyvinyl chloride resin, 25-35 parts of ABS resin, 5-15 parts of polyionic liquid block copolymer, 40-60 parts of carbon black, 20-30 parts of nano magnesium aluminum hydrotalcite, 5-10 parts of nano boron oxide, 5-10 parts of nano zinc oxide, 1-2 parts of plasticizer and 1-2 parts of silane coupling agent.

[0008] Furthermore, the preparation method of the polyionic liquid-containing block copolymer is as follows:

[0009] After dissolving PS-b-PVBCl in a dipolar aprotic solvent, add N-methylimidazole, and react the resulting mixture at 80-100°C for more than 12 hours. After the reaction is completed, add it dropwise to methanol at 0-5°C, filter out the precipitate, and dry it to obtain an intermediate, which is dissolved in a dipolar aprotic solvent, and then add an anion displacer. After stirring for more than 12 hours, add it dropwise to methanol at 0-5°C after the reaction is completed, filter out the precipitate, and dry it.

[0010] Furthermore, the weight ratio of the PS-b-PVBCl to N-methylimidazole is 1:0.25-1.

[0011] Furthermore, the weight ratio of the intermediate to the anion displacer is 1:0.4-1.

[0012] Furthermore, the anion replacer is a potassium salt of a fluorine-containing anion and / or a sodium salt of a fluorine-containing anion.

[0013] Furthermore, the anion replacement agent is any one or more combinations of sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium hexafluoroantimonate, potassium tetrafluoroborate, potassium hexafluorophosphate, potassium trifluoromethanesulfonate, and potassium hexafluoroantimonate.

[0014] Further, the plasticizer is any one or more combinations of di(2-ethylhexyl) phthalate, dioctyl phthalate, di-n-octyl phthalate, butyl benzyl phthalate, di-sec-octyl phthalate, dicyclohexyl phthalate, dibutyl phthalate, diisobutyl phthalate, dimethyl phthalate, diethyl phthalate, diisononyl phthalate, and diisodecyl phthalate.

[0015] Furthermore, the silane coupling agent is silane coupling agent A-171 and / or silane coupling agent A-172.

[0016] Furthermore, a refractory filler is filled between the cable core and the outer refractory layer.

[0017] Furthermore, the refractory filler is aluminum hydroxide and / or magnesium hydroxide.

[0018] Beneficial effects of the present invention:

[0019] The present invention provides a fire-resistant shipboard cable, wherein the outer fire-resistant layer, the inner fire-resistant layer and the fire-resistant filler can protect the cable so that it can be powered on for a long time when burning, so that the crew on board can escape and save themselves within an effective time, thereby improving the survivability;

[0020] ABS resin dispersed in polyvinyl chloride resin acts as a stress concentration center, inducing a large number of silver streaks or shear bands and controlling the development of silver streaks or shear bands. The generation and development of a large number of silver streaks or shear bands consumes a lot of energy, thus significantly improving the mechanical strength of the outer refractory layer and the inner refractory layer;

[0021] The addition of the polyionic liquid block copolymer plays a positive role in improving the mechanical properties of the outer refractory layer and the inner refractory layer, and the flame retardant elements such as N, F, P, and B introduced can enhance the flame retardant properties of the outer refractory layer and the inner refractory layer through the condensation of the carbon layer and the capture of gas phase free radicals.

[0022] Nano magnesium aluminum hydrotalcite decomposes to generate water vapor and carbon dioxide during combustion, thus achieving a flame retardant effect. Its combustion decomposition products have a very strong adsorption effect on the smoke and toxic gases generated by combustion. Nano boron oxide can react with magnesium aluminum hydrotalcite at high temperature to generate aluminum borate and magnesium borate, which can improve the density and continuity of the carbon layer generated by combustion, isolate oxygen, and play a role in inhibiting the combustion reaction.

[0023] On the one hand, refractory fillers can isolate high temperatures, and on the other hand, the decomposition products can dilute combustible gases, reduce oxygen concentration, and thus reduce the combustion rate. They also adhere to the surface of the cable to isolate air and prevent combustion.

[0024] The fire-resistant shipboard cable prepared by the present invention can still maintain normal power supply after burning in a flame of 950-1000° C. for 90 minutes, showing extremely high fire resistance and reaching Class A standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic structural diagram of the fire-resistant shipboard cable provided in Example 1 of the present invention;

[0026] The numbers in the figure represent:

[0027] 1-Copper conductor, 2-Inner fire-resistant layer, 3-PVC inner sheath layer, 4-Refractory filler, 5-Outer fire-resistant layer, 6-Tinned copper mesh shielding layer, 7-PVC outer sheath layer. DETAILED DESCRIPTION

[0028] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0029] Polyvinyl chloride resin: Bio;

[0030] ABS resin: Chimei;

[0031] Block copolymers containing polyionic liquids: homemade;

[0032] Carbon black N770: Huayuan;

[0033] Nano magnesium aluminum hydrotalcite: Hao Ruicheng;

[0034] Nano boron oxide: Tengshuang;

[0035] Nano zinc oxide: Hengge;

[0036] Plasticizer DOP: Qilu Petrochemical;

[0037] Silane coupling agent A-171: Silane Teng.

[0038] Embodiment 1:

[0039] A fire-resistant shipboard cable, comprising a cable core, an outer fire-resistant layer 5, a tinned copper mesh shielding layer 6 and a PVC outer sheath layer 7, magnesium hydroxide is also filled between the cable core and the outer fire-resistant layer 5 as a fire-resistant filler 4, and the cable core is composed of a copper conductor 1, an inner fire-resistant layer 2 and a PVC inner sheath layer 3;

[0040] The outer refractory layer 5 and the inner refractory layer 2 are made of the same material, and include the following components by weight:

[0041] 120 parts of polyvinyl chloride resin, 30 parts of ABS resin, 10 parts of block copolymer containing polyionic liquid, 50 parts of carbon black N770, 20 parts of nano magnesium aluminum hydrotalcite, 10 parts of nano boron oxide, 10 parts of nano zinc oxide, 1 part of plasticizer DOP, and 2 parts of silane coupling agent A-171.

[0042] Wherein, the preparation method of the block copolymer containing polyionic liquid is as follows:

[0043]

[0044] Under nitrogen protection, 12.5g of p-chloromethylstyrene and 37.5g of styrene were mixed, 0.5g of initiator AIBN was added, and the mixture was heated in an oil bath at 80°C for 10h. After the reaction was completed, the product was dissolved in 200ml of tetrahydrofuran, and then added dropwise to 2000ml of 0-5°C methanol. The precipitated white solid was filtered out, washed repeatedly with methanol, and then vacuum dried for 24h to obtain PS-b-PVBCl. 30g of PS-b-PVBCl was dissolved in 200ml of DMF, and then 10g of N-methylimidazole was added. The mixed mixture was heated in an oil bath at 80°C for 24h. After the reaction was completed, it was added dropwise to 2000ml of 0-5°C methanol. The precipitate was filtered out, washed repeatedly with methanol, and then vacuum dried for 24h to obtain an intermediate. 20g of the intermediate was dissolved in 200ml of DMF, and then 10g of potassium tetrafluoroborate was added. The reaction was stirred for 24h. After the reaction was completed, it was added dropwise to 2000ml The precipitate was filtered out in methanol at 0-5°C, washed repeatedly with methanol and dried under vacuum for 24 hours.

[0045] The preparation method of the above-mentioned fire-resistant marine cable is as follows:

[0046] The copper monofilament is drawn to a diameter of 2.5-2.75 mm, annealed at 400° C. for 1 h, and then twisted into a copper conductor 1. Polyvinyl chloride resin, ABS resin, block copolymer containing polyionic liquid, carbon black N770, nano magnesium aluminum hydrotalcite, nano boron oxide, nano zinc oxide, plasticizer DOP, and silane coupling agent A-171 are mixed and melt-extruded at 200° C. to obtain refractory granules. The extruder speed is 60 r / min. The refractory granules and PVC material are sequentially extruded on the copper conductor 1 to obtain a cable core including an inner refractory layer 2 and a PVC inner sheath layer 3. Four strands of the cable core are twisted and then extruded with an outer refractory layer 5. Magnesium hydroxide is filled between the cable core and the outer refractory layer 5 as a refractory filler 4. A tinned copper mesh shielding layer 6 is woven on the surface of the outer refractory layer 5 with a weaving density of 83%. Finally, a PVC outer sheath layer 7 is extruded.

[0047] Embodiment 2:

[0048] The method is basically the same as Example 1, except that the outer refractory layer and the inner refractory layer are made of the same material, and include the following components by weight:

[0049] 120 parts of polyvinyl chloride resin, 35 parts of ABS resin, 15 parts of polyionic liquid block copolymer, 60 parts of carbon black N770, 30 parts of nano magnesium aluminum hydrotalcite, 5 parts of nano boron oxide, 10 parts of nano zinc oxide, 1 part of plasticizer DOP, and 1 part of silane coupling agent A-171.

[0050] Embodiment 3:

[0051] The method is basically the same as Example 1, except that the outer refractory layer and the inner refractory layer are made of the same material, and include the following components by weight:

[0052] 100 parts of polyvinyl chloride resin, 25 parts of ABS resin, 5 parts of block copolymer containing polyionic liquid, 40 parts of carbon black N770, 20 parts of nano magnesium aluminum hydrotalcite, 5 parts of nano boron oxide, 5 parts of nano zinc oxide, 1 part of plasticizer DOP, and 1 part of silane coupling agent A-171.

[0053] Embodiment 4:

[0054] The method is substantially the same as Example 1, except that potassium tetrafluoroborate is replaced by sodium hexafluorophosphate.

[0055] Comparative Example 1:

[0056] The method is substantially the same as Example 1, except that no polyionic liquid-containing block copolymer is added.

[0057] Comparative Example 2:

[0058] The method is basically the same as Example 1, except that nano-magnesium-aluminum hydrotalcite is not added.

[0059] Comparative Example 3:

[0060] The method is basically the same as Example 1, except that nano boron oxide is not added.

[0061] Comparative Example 4:

[0062] The method is basically the same as Example 1, except that nano zinc oxide is not added.

[0063] Performance Testing:

[0064] The refractory granules prepared in Examples 1-4 and Comparative Examples 1-4 were used as samples for performance testing;

[0065] ① Test the tensile strength of the sample in accordance with GB / T 1040-2018 "Determination of tensile properties of plastics";

[0066] Limiting oxygen index: Refer to GB / T 2406.1-2008 "Determination of combustion behavior of plastics by oxygen index method" to test the limiting oxygen index;

[0067] Determination of the number of molten droplets: Ignite the sample and measure the number of molten droplets within 120 seconds of combustion.

[0068] ② The fire-resistant marine cables prepared in Examples 1-4 and Comparative Examples 1-4 were used as samples for fire resistance tests;

[0069] Fire resistance test: Place the sample in a flame at 950-1000℃ and record the time the sample remains normally powered.

[0070] The test results are shown in Table 1:

[0071] Table 1:

[0072]

[0073] It can be seen from Table 1 above that the fire-resistant shipboard cable prepared by the present invention can still maintain normal power supply after burning in a flame of 950-1000°C for 90 minutes, showing extremely high fire resistance and reaching Class A standards.

[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A fire-resistant shipboard cable, characterized in that: It comprises a cable core, an outer fire-resistant layer, a shielding layer and an outer sheath layer, wherein the cable core is composed of a conductor, an inner fire-resistant layer and an inner sheath layer; The outer refractory layer and the inner refractory layer are made of the same material, and include the following components by weight: 100-120 parts of polyvinyl chloride resin, 25-35 parts of ABS resin, 5-15 parts of polyionic liquid block copolymer, 40-60 parts of carbon black, 20-30 parts of nano magnesium aluminum hydrotalcite, 5-10 parts of nano boron oxide, 5-10 parts of nano zinc oxide, 1-2 parts of plasticizer, and 1-2 parts of silane coupling agent; The preparation method of the polyionic liquid-containing block copolymer is as follows: Under nitrogen protection, 12.5 g of p-chloromethylstyrene and 37.5 g of styrene were mixed, 0.5 g of initiator AIBN was added, and the mixture was heated in an oil bath at 80 °C for 10 h. After the reaction was completed, the product was dissolved in 200 ml of tetrahydrofuran, and then added dropwise to 2000 ml of 0-5 °C methanol. The precipitated white solid was filtered out, washed repeatedly with methanol, and then vacuum dried for 24 h to obtain PS-b-PVBCl; After dissolving PS-b-PVBCl in a dipolar aprotic solvent, add N-methylimidazole, and react the resulting mixture at 80-100°C for more than 12 hours. After the reaction is completed, add it dropwise to methanol at 0-5°C, filter out the precipitate, and dry it to obtain an intermediate, which is dissolved in a dipolar aprotic solvent, and then add an anion displacer. After stirring for more than 12 hours, add it dropwise to methanol at 0-5°C after the reaction is completed, filter out the precipitate, and dry it.

2. The fire-resistant shipboard cable according to claim 1, characterized in that: The weight ratio of the PS-b-PVBCl to N-methylimidazole is 1:0.25-1.

3. The fire-resistant shipboard cable according to claim 1, characterized in that: The weight ratio of the intermediate to the anion replacement agent is 1:0.4-1.

4. The fire-resistant shipboard cable according to claim 1, characterized in that: The anion displacer is a potassium salt of a fluorine-containing anion and / or a sodium salt of a fluorine-containing anion.

5. The fire-resistant shipboard cable according to claim 4, characterized in that: The anion replacement agent is any one or more combinations of sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium hexafluoroantimonate, potassium tetrafluoroborate, potassium hexafluorophosphate, potassium trifluoromethanesulfonate, and potassium hexafluoroantimonate.

6. The fire-resistant shipboard cable according to claim 1, characterized in that: The plasticizer is di(2-ethylhexyl) phthalate, dioctyl phthalate, butyl benzyl phthalate, di-sec-octyl phthalate, dicyclohexyl phthalate, dibutyl phthalate, Any one or more combinations of diisobutyl phthalate, dimethyl phthalate, diethyl phthalate, diisononyl phthalate and diisodecyl phthalate.

7. The fire-resistant shipboard cable according to claim 1, characterized in that: The silane coupling agent is silane coupling agent A-171 and / or silane coupling agent A-172.

8. The fire-resistant shipboard cable according to claim 1, characterized in that: A refractory filler is also filled between the cable core and the outer refractory layer.

9. The fire-resistant shipboard cable according to claim 8, characterized in that: The refractory filler is aluminum hydroxide and / or magnesium hydroxide.

Citation Information

Patent Citations

  • Flame-retardant antistatic high-strength thermoplastic composite material and its preparation method

    CN102850646A

  • Ratproof anti-termite mildew-resistant environment-friendly power cable material

    CN107082972A

  • Fire resistant cable

    KR1020120002817A